Brand choice and preference segmentation in South African luxury car market - Hani, Muhammad Ali (My University, 2015)
The luxury car market in South Africa accounts for 18 per cent of total automobile market and is growing fast. Manufacturers and marketers need to understand attributes people consider when buying a luxury car. The purpose of this study is to provide insights of consumer behavior when buying a luxury car and assist manufacturers and marketers to understand more in depth on the attributes that may attract and influence consumers. A conjoint analysis was used to identify the attributes influencing the buyers’ behavior and to determine their relative importance. Furthermore, a cluster analysis was used to segment the luxury market into different clusters. Finally, descriptive analysis was used to identify customer loyalty in this market. The results showed that consumers in South Africa consider body-type, brand, distinctive features and engine capacity to be the most important attributes influencing their purchasing decisions. Based on these attributes, the market was divided into five segments and demographics of these segments were explained. In the end, the study revealed that brand loyalty exist in most of the luxury brands in South Africa.
Keywords: Consumer behavior -- South Africa.Consumers' preferences -- South Africa. Brand choice -- South Africa. Automobile industry and trade -- South Africa.